OCORRÃŠNCIA DO NEMATÃ“IDE DE CISTO, ð˜ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜¢ ð˜¨ð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ð˜´ ICHINOHE, 1952, EM CULTURA DE SOJA, NO ESTADO DE SÃƒO PAULO - Rossi, Carlos Eduardo; Monteiro, Ailton Rocha; Ramiro, Zuleide Alves (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA DO NEMATÃ“IDE DE CISTO, ð˜ð˜¦ð˜µð˜¦ð˜³ð˜°ð˜¥ð˜¦ð˜³ð˜¢ ð˜¨ð˜ð˜ºð˜¤ð˜ªð˜¯ð˜¦ð˜´ ICHINOHE, 1952, EM CULTURA DE SOJA, NO ESTADO DE SÃƒO PAULO